Transcription Regulator YgeK Affects the Virulence of Avian Pathogenic Escherichia coli - Jian Tu; Dandan Fu; Yi Gu; Ying Shao; Xiangjun Song; Mei Xue; Kezong Qi (Animals, 2021)
Avian pathogenic Escherichia coli (APEC) is the responsible pathogen for colibacillosis in poultry, and is a potential gene source for human extraintestinal pathogenic Escherichia coli. Escherichia coli type III secretion system 2 (ETT2) is widely distributed in human and animal ExPEC isolates, and is crucial for the virulence of ExPEC. Transcriptional regulator YgeK, located in the ETT2 gene cluster, was identified as an important regulator of gene expression in enterohemorrhagic E. coli (EHEC). However, the role of YgeK in APEC has not been reported. In this study, we performed amino acid alignment analysis of YgeK among different E. coli strains and generated ygeK mutant strain AE81ΔygeK from clinical APEC strain AE81. Flagellar formation, bacterial motility, serum sensitivity, adhesion, and virulence were all significantly reduced following the inactivation of YgeK in APEC. Then, we performed transcriptome sequencing to analyze the functional pathways involved in the biological processes. Results suggested that ETT2 transcriptional regulator YgeK plays a crucial role in APEC virulence. These findings thus contribute to our understanding of the function of the ETT2 cluster, and clarify the pathogenic mechanism of APEC.